Relevansi Pemikiran Ekosufisme Abdul Karim Al-Jilli pada Gerakan Ekoteologi Di Indonesia - Mustofah, Misbahul; Dwi Agustin, Yolanda (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2025)
The ongoing environmental degradation indicates a shift in humanity’s religious paradigm. While religion teaches the importance of preserving and nurturing nature, in practice, humans often exploit and damage the environment. This study aims to examine the eco-Sufist thought of Abdul Karim al-Jilli, particularly through his concept of Insan Kamil (the Perfect Human), and explore its relevance to the Islamic ecotheological movement in Indonesia. This qualitative research employs a library research method, utilizing various sources such as books, journals, and scholarly articles. The findings reveal that al-Jilli’s eco-Sufism perceives humans as the highest manifestation of divine self-disclosure (tajalli Ilahi), bearing both spiritual and moral responsibilities toward the universe. The concept of Insan Kamil embodies ecological consciousness through principles such as balance, responsibility, and love for all creation. In the Indonesian context, this aligns with the spirit of Islamic ecotheology, which promotes ecological piety grounded in religious doctrine. To reach the level of Insan Kamil, individuals must undergo spiritual transformation through the stages of takhalli, tahalli, and tajalli. Thus, al-Jilli’s thought provides a theological foundation for developing an integrated environmental ethic that connects God, humans, and nature.